METODE PENDIDIKAN ISLAM PERSPEKTIF HADITS - Mufaizin Mufaizin (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2018)
The education method is one of the things that determine the success of education in addition to material, media, and evaluation. From many factors causing failure in education, education method is one of the most dominant factors. As good as any education purposes, if not supported by appropriate methods are very difficult to achieve well. It is often mentioned that “al-thariqah ahammu min al-maddah”, (method is sometimes more important than material). Therefore the maintenance of Islamic education methods should be done carefully accordingto various related factors so that the results of education are satisfactory. Prophet Muhammad SAW as the last man chosen by Allah SWT to deliver His message, since the beginning have exemplified in implementing the correct method of Islamic education with his Sahabah. He did Learning strategy in conveying his teachings of Islam such as he is very concerned about the situation, condition and character of person. Prophet Muhammad SAW is ideal teacher and perfect figureso that Islamic values can be well transferred. Prophet Muhammad SAW also understandsinstinct and condition of each person so that anyone who gets enlightenment and education from him easily absorbs perfectly and receives it with pleasure and cordiality.